Sistem Pengelolaan Pendidikan Pesantren Putri Daarul Qolam Madrasah Aliyah Negeri Tempursari Mantingan Ngawi Jawa Timur Tahun 2015 - Masrurotin, Malik, Dr. Sudarno Shobron, M.Ag, Dr. Sabar Narimo, M.M, M.Pd (2016)
Development of Islamic boarding school has alteration in the leadership, from individualistic becomes collective in the institute. This alteration brings implication into management system which more professional, stuctural and each job is clear. Alteration system in Islamic boarding school is ponse to phenomenom wich happen to society, that is pretention of society for making them self as useful human, who understand about their reality, has high morality,and understand about religion, between modernity and hegemony of west culture. For responding that phenomenom, appear new development in Islamic boarding school word that is estabilishment Islamic boarding school in Islamic school whish has uniqueness and characteristic of it. Focus in this research means how is system and education management model of Islamic boarding school of state Islamic high school Daarul Qolam Tempursari Mantingan Ngawi and what is the factor of proponent and abstacle. The object of this research means for knowing the system and education management model of Islamic Boarding School of state Islamic high school Daarul Qolam Tempursari Mantingan Ngawi and what is the factor of proponent and obstacle. Kind of this research is field research which is in Islamic boarding school of state Islamic high school Daruul Qolam Tempursari Mantingan Ngawi. Approachment in this research uses participant observation technic and case studying plan. Accumulation technic is done by visceral interview participant of documentation studying. The election of research informant by purposif technic is fused with snowbal sampling. After accumulating data by means of all of the technic after word that is examined its legality, data is examined by data reduction way, data presentation and conclusion drawing. The result of this research is that the management of education planning with the preparation of lesson schedule, organizing the division of functions, duties, authority and responsibilities of each staff boarding, leadership clerics involving subordinates in control, evaluation and corrective action activities Pesantren Putri Daarul Qolam MAN Tempursari Mantingan Ngawi. Parenting Pesantren Putri Daarul Qolam Tempursari Mantingan MAN Ngawi with the system of delegation nanny / leader to the head of the cottage and teacher coaches. Islamic activities which is full supported by the headmaster of Islmic school, parent of student and enthusiasm of student, and the obtacles of the management are the condition of dormitory of Islamic boarding school and the supporting facility which is less proper and the program whis collides with Islamic school program.